Pengaruh Celebrity Endorser dan Citra Merek Terhadap Keputusan Pembelian Iphone - Alfiansyah, Fito; Prakoso, Fajar Adi (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2025)
This study is titled "The Influence of Celebrity Endorser and Brand Image on Purchase Decisions for iPhones among FEB UMJ Students." The research aims to determine the influence of Celebrity Endorsers and Brand Image on the purchase decisions for iPhones among FEB UMJ students. This research employs a quantitative method with an associative approach. The population consists of FEB UMJ students who use iPhones. The sampling technique used is purposive sampling, with a total sample size of 80 respondents determined using the Slovin formula for FEB UMJ students who use iPhones. Data analysis was conducted using Smart PLS 3.0 software. Data collection techniques involved distributing questionnaires via Google Forms to FEB UMJ students who use iPhones. The results of the study show that the Celebrity Endorser variable has a positive and significant influence on Purchase Decisions, with a significance result of 0.002 in the hypothesis test. Similarly, the Brand Image variable also has a positive and significant influence on Purchase Decisions, with a significance value of 0.004 in the hypothesis test. Based on the R Square results, it is evident that Celebrity Endorser and Brand Image influence iPhone Purchase Decisions by 51%.